P20 BRACHIAL AND RADIAL SYSTOLIC BLOOD PRESSURE ARE NOT THE SAME: POTENTIAL IMPLICATIONS FOR VALIDATION PROTOCOLS INCLUDING BRACHIAL CUFF DEVICES AND WRIST-BASED WEARABLES - Matthew Armstrong; Martin Schultz; Dean Picone; James Sharman; Nathan Dwyer; Philip Roberts-Thomson; Andrew Black (Artery Research, 2018)
Introduction: Radial intra-arterial blood pressure (BP) is sometimes used as the reference standard for validation of brachial cuff BP devices, and there is an emerging ‘wearables’ market seeking to measure BP at the wrist. However, brachial systolic BP may not be a good representation of the radial systolic BP, and this could have implications for appropriate BP validation protocols. This study sought to determine the difference between brachial and radial systolic BP. Methods: Intra-arterial BP was measured consecutively at the brachial and radial arteries in 168 participants undergoing coronary angiography (aged 62 ± 10 years, 69% male). Intra-arterial BP recordings were made via fluid filled catheter according to guideline recommendations. Results: Brachial systolic BP was lower than radial systolic BP (136.5 vs 143.9 mmHg; p<0.001). Only 40% of participants had a brachial systolic BP within ±5 mmHg to radial systolic BP (138.1 and 138.5 mmHg, p = 0.15). Additionally, 25% and 17% of participants had systolic BP differences of 5 to 10 mmHg (132.7 and 139.9 mmHg respectively, p < 0.001) and 10 to 15 mmHg (132.2 and 144.4 mmHg respectively; p < 0.001). A further 18% had systolic BP differences >15 mmHg (140.3 and 161.3 mmHg; p < 0.001). Conclusion: Radial systolic BP is not representative of brachial systolic BP, with the majority of participants having a systolic BP difference greater than 5 mmHg between brachial and radial arteries. Therefore, if validation testing of BP devices is performed with intra-arterial BP as the reference standard, this should be undertaken at the same site as the brachial cuff or wrist based wearable device.